2013
DOI: 10.3897/zookeys.365.6202
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding and the differentiation between North American and West European Phormia regina (Diptera, Calliphoridae, Chrysomyinae)

Abstract: Phormia regina (the black fly) is a common Holarctic blow fly species which serves as a primary indicator taxon to estimate minimal post mortem intervals. It is also a major research model in physiological and neurological studies on insect feeding. Previous studies have shown a sequence divergence of up to 4.3% in the mitochondrial COI gene between W European and N American P. regina populations. Here, we DNA barcoded P. regina specimens from six N American and 17 W European populations and confirmed a mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…We propose using the nuclear internal transcribed spacer ITS2 as a second barcoding locus for taxonomic species determinations in calliphorids as suggested by GilArriortua et al (2014) . Although evaluations of ITS2 as unique identification marker have limitations for some taxa ( Agnarsson, 2010 ), several studies have shown the potential application of ITS2 for blowfly species identification ( Jordaens et al, 2013a ; Nelson, Wallman & Dowton, 2007 ; Nelson, Wallman & Dowton, 2008 , Song, Wang & Liang, 2008 ; Yusseff-Vanegas & Agnarsson, 2016 ). We expect a combination of barcodes from the nuclear and mitochondrial genomes to offer a general, simple and reliable way of identifying forensically important insects, even problematic sister species, as successfully done in certain other arthropod groups ( Anslan & Tedersoo, 2015 ; Cao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…We propose using the nuclear internal transcribed spacer ITS2 as a second barcoding locus for taxonomic species determinations in calliphorids as suggested by GilArriortua et al (2014) . Although evaluations of ITS2 as unique identification marker have limitations for some taxa ( Agnarsson, 2010 ), several studies have shown the potential application of ITS2 for blowfly species identification ( Jordaens et al, 2013a ; Nelson, Wallman & Dowton, 2007 ; Nelson, Wallman & Dowton, 2008 , Song, Wang & Liang, 2008 ; Yusseff-Vanegas & Agnarsson, 2016 ). We expect a combination of barcodes from the nuclear and mitochondrial genomes to offer a general, simple and reliable way of identifying forensically important insects, even problematic sister species, as successfully done in certain other arthropod groups ( Anslan & Tedersoo, 2015 ; Cao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported on barcoding results for Coleoptera (Hendrich et al, 2015;Raupach, Hannig, Moriniere, & Hendrich, 2016;Raupach, Hannig, Morinière, & Hendrich, 2018;Rulik et al, 2017), Ephemeroptera, Plecoptera and Trichoptera , Heteroptera (Havemann et al, 2018;Raupach et al, 2014), Hymenoptera (Schmid-Egger et al, 2019;Schmidt, Schmid-Egger, Morinière, Haszprunar, & Hebert, 2015;Schmidt et al, 2017), Lepidoptera Hausmann, Haszprunar, Segerer, et al, 2011), Neuroptera , Orthoptera (Hawlitschek et al, 2017), Araneae and Opiliones , and Myriapoda (Spelda, Reip, Oliveira Biener, & Melzer, 2011;Wesener et al, 2015). Concerning DNA barcoding studies performed for Diptera, no comprehensive study encompassing this entire highly diverse order has been published, but data have been used to revise smaller units thereof: for example, for Calliphoridae (Jordaens et al, 2013;Nelson, Wallman, & Dowton, 2007;Reibe, Schmitz, & Madea, 2009), Ceratopogonidae (Stur & Borkent, 2014), Chironomidae (Carew, Pettigrove, Cox, & Hoffmann, 2007;Carew, Pettigrove, & Hoffmann, 2005;Cranston et al, 2013;Ekrem, Stur, & Hebert, 2010;Ekrem, Willassen, & Stur, 2007;Montagna, Mereghetti, Lencioni, & Rossaro, 2016;Pfenninger, Nowak, Kley, Steinke, & Streit, 2007;Sinclair & Gresens, 2008;Stur & Ekrem, 2011), Culicidae (Ashfaq et al, 2014;Cywinska, Hunter, & Hebert, 2006;Kumar, Rajavel, Natarajan, & Jambulingam, 2007;Versteirt et al, 2015;, Hybotidae…”
mentioning
confidence: 99%
“…Some of these studies also identified decomposition stages and the corresponding role of necrophagous insects [25,31]. These approaches can be complemented with molecular biology, such as cytochrome c oxidase I (COI) DNA barcoding [32][33][34][35][36], which can facilitate an accurate and reliable identification of forensically important insects from human or animal carcasses.…”
Section: Introductionmentioning
confidence: 98%